xEV Landscape in India and Future Trends - Hazra, Sandip; Khan, Arkadip (New Energy Exploitation and Application, 2025)
The electric and hybrid vehicles (xEVs) market in India is moving quickly due to enabling regulatory frameworks, ongoing technology developments and the preferences of buyers. It focuses on all the factors affecting India’s progress in xEVs by examining trends in use, government schemes such as FAME and the benefits provided by each state. In 2024, sales of electric vehicles (EVs) in India surpassed 1.95 million units which was 27% higher than the previous year and experts estimate up to 30% of the four wheeler (4W) segment to be electrified by 2030 under supportive policies, more than double the expected number without such policies. A thorough PESTEL assessment determines the main factors that influence EVs such as more charging stations (the number increased 80 times since 2015), issues with obtaining batteries in sufficient quantities, the high price of EVs and how consumers’ views are constantly shifting toward them. Artificial Intelligence and machine learning (AI/ML) methods are used to understand what is likely to drive the market and how government policies and infrastructure development are essential for promoting electrification. The report also analyzes battery improvement, declining battery prices and what emissions mean over the lifecycle, all of which give useful guidance for creating a greener environment for electric cars across India. Linking data with impact evaluation, the research gives a complete understanding of India’s move toward electric vehicles and their impact on green transportation.